Proactive spectrum sensing and spectrum sharing for cognitive radio - Ian Bajaj (2012)
Cognitive radio (CR) is emerging as a field essential to the progress of wireless communications. With spectral efficiency at the forefront in protocol design, CR aims in combating the supposed spectrum crisis due to inefficiency in spectral utilization. Thus a lot more spectrum-hungry services can be supported by the limited frequency bands through opportunistic access or sharing of licensed spectrum. As spectrum sensing precedes any possible access or sharing of spectrum, it is crucial that the sensing result is accurate when the initial sensing decision is made. Most of the current sensing techniques are passive in nature (i.e. they do not involve any participation of the CR) and hence can incur sensing errors when eavesdropping in the midst of high-noise or fading environments. Thus we consider a novel proactive spectrum sensing scheme that increases the certainty in the spectrum decision while combating the hidden-node problem. This is achieved when the CR sends out a probing signal prior to the sensing process. We study the results of applying power constraints to the power available for probing, and see how this scheme proves beneficial to the licensed user (LU) in terms of greater protection while still maintaining the throughput needs of the CR.